(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This research article delves into the comparative study of the national-cultural characteristics of the Uzbek and English languages, particularly focusing on affectionate expressions. It explores how language encapsulates cultural identity and emotional nuances influenced by historical and socio-cultural contexts. By analyzing linguistic phenomena such as zoonyms, plant metaphors, and food-related terms, the study uncovers universal patterns and cultural distinctions in how affection is expressed. Findings highlight the differences in linguistic practices shaped by typological systems—agglutinative in Uzbek and analytical in English—and their respective cultural paradigms rooted in agricultural and urban-industrial traditions. The research underscores the practical implications for translation, education, and intercultural communication.